The Development of 4D BIM Based Infrastructure Construction Time Planning Standard Operating Procedure to Enhance Communication Quality from Infrastructure Contractor Perspective - Almadani Jayadi; Leni Sagita Riantini (AIBPM Publisher, 2019)
4D BIM can be utilized as a visual communication media that simulates construction process, including infrastructure projects, to all stakeholders. One of its benefits is to enhance communication quality that can positively affect infrastructure construction time planning phase, which was one of the most important aspect in contractor’s business process. This research used qualitative method through interviews and expert validation to identify main activities in construction time planning phase, 4D BIM role in those activities, and involved stakeholders. As a result, 4D BIM based construction time planning strategy in the form of standard operating procedure and communication flow was developed to be used as guideline references for BIM implementation in Indonesia.